ESTIMASI STOK KARBON PADA BIOMASSA LAMUN DI PULAU KEDINDINGAN, KALIMANTAN TIMUR - Ambomasse, Yusril M.; Irawan, Aditya; Paputungan, Mohammad Sumiran; Rahmawati, Susi (Coastal and Ocean Journal (COJ), 2024)
Kedindingan Island is a part of marine conservation area in East Kalimantan. This island has a seagrass ecosystem, which could potentially provide ecosystem service in climate change mitigation as a carbon sink. However, there is limited information on the carbon content of the seagrass ecosystem there. This study aimed to estimate the carbon stock in the seagrass biomass on Kedindingan Island. Field sampling activities for collecting seagrass biomass were done in September 2021. A PVC core with a 20 cm diameter, 3 mm thick, and 80 cm length was used to collect seagrass biomass. The loss on ignition (LOI) method was applied to determine the concentration of organic carbon in the biomass. The results of this study found 7 species of seagrass in the study area, which were dominated by Thalassia hemprichii. The organic carbon concentration in above-ground biomass and below-ground biomass ranged from 30.8-31.7% and 29.4-31.4%, respectively. The average biomass was 4.99 Mg/ha and its average carbon stock was estimated at 1.53 MgC/ha. Based on the total carbon stock analysis, the above-ground biomass stored more carbon (79.28%) than the below-ground biomass.